Ecological Impacts of Lamprey Based on Lotka-Volterra Model - Wu, Yuzhe; Li, Xinyi; Zhang, Qiwei (Transactions on Environment, Energy and Earth Sciences, 2024)
Unlike most organisms, lampreys have a unique ability to change their sex based on the status of environmental resources. This study aims to investigate the intrinsic relationships between species within an ecosystem and to assess the advantages and disadvantages of lampreys’ ability to change sex. A Gender Determination Model was established to represent the interaction between lamprey populations and the environment. This article used three evaluation criteria, including the impact on environmental conditions, performance in interspecies competition, and the Shannon-Wiener index. The Dynamic Model of Lamprey and Parasite populations was developed to explore the impact of the lamprey’s sex change mechanism on parasites within the ecosystem. by adjusting parameters to represent different parasitic states, by comparing situations with and without lamprey gender transformation mechanisms. We drawn the conclusion that, regardless of the type of parasite, none gained an advantage when lampreys had gender transformation mechanisms. Finally, this article obtained the sensitivity analysis curves for population size and environmental condition in MATLAB. This article elucidates the intricate interplay between the sex determination mechanism of lampreys and environmental resources, offering a novel perspective on the role of sexual plasticity within ecosystems. Particularly against the backdrop of increasing human activities that impact the natural ecological balance, understanding these interactions can facilitate more effective conservation and management of species that rely on specific sex ratios or particular population dynamics.